Additive manufacturing of shape memory polymers: effects of print orientation and infill percentage on shape memory recovery properties - Villacres, Jorge; Nobes, David; Ayranci, Cagri (Rapid prototyping journal, 2020)
Purpose The purpose of this paper is to study the shape memory properties of SMP samples produced through a MEAM process. Fused deposition modeling or, as it will be referred to in this paper, material extrusion additive manufacturing (MEAM) is a technique in which polymeric materials are extruded though a nozzle creating parts via accumulation and joining of different layers. These layers are fused together to build three-dimensional objects. Shape memory polymers (SMP) are stimulus responsive materials, which have the ability to recover their pre-programmed form after being exposed to a large strain. To induce its shape memory recovery movement, an external stimulus such as heat needs to be applied. Design/methodology/approach This project investigates and characterizes the influence of print orientation and infill percentage on shape recovery properties. The analyzed shape recovery properties are shape recovery force, shape recovery speed and time elapsed before activation. To determine whether the analyzed factors produce a significant variation on shape recovery properties, t-tests were performed with a 95% confidence factor between each analyzed level. Findings Results proved that print angle and infill percentage do have a significant impact on recovery properties of the manufactured specimens. Originality/value The manufacturing of SMP objects through a MEAM process has a vast potential for different applications; however, the shape recovery properties of these objects need to be analyzed before any practical use can be developed. These have not been studied as a function of print parameters, which is the focus of this study.